A case report of primary adrenal angiosarcoma as depicted on magnetic resonance imaging. Issue 45 (November 2017) - Li, Xue-Ming; Yang, Hong; Reng, Jing; Zhou, Peng; Cheng, Zhu-Zhong; Li, Zhen; Xu, Guo-Hui
Abstract: Rationale: Angiosarcoma is an extremely rare malignant tumor of endothelial origin. The majority of studies reporting angiosarcoma have been concerned with the clinical and pathological aspects, with limited reporting of their imaging findings. To our knowledge, angiosarcoma of the adrenal gland is very rare. Herein we firstly report a primary adrenal angiosarcoma depicted on magnetic resonance imaging (MRI). Patient concerns: A 59-year-old man was referred to our hospital for 1 year left-flank pain that exacerbated in recent 4 months. Diagnosis: A regular mass with clear boundary was revealed on MRI in the region of left adrenal gland. Its signal intensity was inhomogeneous. It mainly showed isointensity with patchy slight hyperintensity on T1-weighted images and marked hyperintensity with patchy hypointensity on T2-weighted images. On contrast-enhanced images, it demonstrated significantly heterogeneous enhancement, and the peripheral solid component showed delayed enhancement. Bulky blood vessels and hemorrhage were identified in the tumor. Interventions: The mass was surgically excised under a left laparoscopic adrenalectomy. Outcomes: Left adrenal angiosarcoma was confirmed by pathological and immunohistochemical examinations. No evidence of recurrence was found 6 months after operation. Lessons: In conclusion, primary adrenal angiosarcoma has some MRI features corresponding to its pathological nature. It should be included in the differential diagnosis when a mass was detected in the adrenal gland.